Associations Between Sleep Duration, Wake-Up Time, Bedtime, and Abdominal Obesity: Results From 9559 Chinese Children Aged 7–18 Years - Liu, Meijuan; Cao, Bingyan; Luo, Qipeng; Wang, Qiao; Liu, Min; Liang, Xuejun; Wu, Di; Li, Wenjing; Su, Chang; Chen, Jiajia; Gong, Chunxiu (Frontiers in Endocrinology, 2021)
Objective: To investigate the associations of sleep duration, wake-up time, bedtime, and childhood abdominal obesity, and to test whether there is a weekday/weekend difference and the potential modifying role of sex. Methods: This cross-sectional study was based on the Students’ Constitution and Health Survey and included 9559 students (4840 boys and 4719 girls) aged 7–18 years (7227 aged 7–12 years, 2332 aged 13–18 years). They were divided into two groups (control group and group with abdominal obesity). The physical measurements included children and youth body height, body weight, and waist circumference (WC). A parent-report questionnaire was used to collect the information about parent characteristics as well as lifestyle and sleep patterns (sleep duration, bedtime, and wake-up time of weekdays and weekends) of children and youth. Results: The prevalence of abdominal obesity was 30.57% and the percentages of sleep duration <9 hours/day, wake-up time before 07:00 am on weekdays and weekends, bedtime after 10:00 pm on weekends were significantly higher in the group with abdominal obesity. After adjusting for confounders, sleep duration <9 hours/day on weekends was inversely related to abdominal obesity in the overall subjects, regardless of their sex and age, while bedtime after 10:00 pm on weekends was inversely related to abdominal obesity only in the overall subjects, boys, and children aged 7–12 years. Logistic regression models in all subjects showed that shorter hours of weekends sleep duration were associated with greater risks of abdominal obesity, even after adjusting for all confounders, including wake-up time and bedtime. The adjusted odds ratios and 95% confidence intervals of abdominal obesity (with ≥10 hours/day as the reference group) for children with 9–10 hours/day, 8–9 hours/day, and <8 hours/day of weekend sleep duration were 1.23 (1.04–1.46), 1.59 (1.32–1.91) and 1.83 (1.42–2.36), respectively. Specifically, after stratification by sex and age, this phenomenon was only observed in boys and children aged 7–12 years. Conclusions: Sleep duration and bedtime on weekends were independently associated with the risk of childhood abdominal obesity, particularly in boys and children aged 7–12 years.